Responses Toward Injustice Shaped by Justice Sensitivity – Evidence From Germany - Bondü, Rebecca; Holl, Anna K.; Trommler, Denny; Schmitt, Manfred J. (Frontiers in Psychology, 2022)
Anger, indignation, guilt, rumination, victim compensation and perpetrator punishment are considered primary responses underlying justice sensitivity (JS). However, injustice and high JS may predispose to further responses. We had N=293 adults rate their JS, 17 potential responses towards 12 unjust scenarios from the victim’s, observer’s, beneficiary’s and perpetrator’s perspective, and several control variables. Unjust situations generally elicited many affective, cognitive, and behavioral responses. JS generally predisposed to strong affective responses towards injustice including sadness, pity, disappointment, and helplessness. It impaired trivialization, victim blaming, or justification, that may otherwise help coping with injustice. It predisposed to conflict solution and victim compensation. Particularly victim and beneficiary JS had stronger effects in unjust situations from the corresponding perspective. These findings add to a better understanding of the main and interaction effects of unjust situations from different perspectives and the JS facets, differences between JS facets, and links between JS and behavior and well-being.